Basic chemistry - Malone, Leo J. , 1938-; Dolter, Theodore O. , 1965-; Gentemann, Steve (John Wiley & Sons, 2013)
Basic Concepts of Chemistry will provide the necessary forum for students to master fundamental problem solving skills, through the framework of outcomes assessment. This framework breaks the chapters into parts and sections and maps these parts to learning objectives to drive home the content to students in "bite-size chunks"